Suitability of the Nisin Z-producer Lactococcus lactis subsp. lactis CBM 21 to be Used as an Adjunct Culture for Squacquerone Cheese Production - Lorenzo Siroli; Francesca Patrignani; Margherita D’Alessandro; Elisa Salvetti; Sandra Torriani; Rosalba Lanciotti (Animals, 2020)
This research investigated the technological and safety effects of the nisin Z producer Lactococcus lactis subsp. lactis CBM 21, tested as an adjunct culture for the making of Squacquerone cheese in a pilot-scale plant. The biocontrol agent remained at a high level throughout the cheese refrigerated storage, without having a negative influence on the viability of the conventional Streptococcus thermophilus starter. The inclusion of CBM 21 in Squacquerone cheesemaking proved to be more effective compared to the traditional one, to reduce total coliforms and Pseudomonas spp. Moreover, the novel/innovative adjunct culture tested did not negatively modify the proteolytic patterns of Squacquerone cheese, but it gave rise to products with specific volatile and texture profiles. The cheese produced with CBM 21 was more appreciated by the panelists with respect to the traditional one.